Pengaruh PENGARUH CELEBRITY ENDORSEMENT TERHADAP PURCHASE INTENTION MELALUI BRAND IMAGE SEBAGAI VARIABEL INTERVENING PADA PRODUK POND’S (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Kutai Kartanegara): Celebrity Endorsement, Brand Image, Purchase Intention - Azizah, Aufa Niswatul; Handayani, Pinto Rukmi; S, Syahruddin (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2024)
This research aims to determine the influence of celebrity endorsements on purchase intention through brand image as an intervening variable (case study of students from the Faculty of Economics and Business who use Pond's products). The population in this study were students from the Faculty of Economics and Business, Kutai Kartanegara University who used pond's products. The research sample was 83 students who used Pond's products. Sampling used Non Probability Sampling techniques with Purposive Sampling type and data analysis tools using Structural Equation Modeling (SEM) using Smart PLS version 4 software. The results of the research show that Celebrity Endorsements have an effect on Purchase Intention. Celebrity Endorsement influences Brand Image. Brand Image influences Purchase Intention. Celebrity Endorsement influences Purchase Intention through Brand Image.